Dry deposition and canopy uptake in Mediterranean holm-oak forests estimated with a canopy budget model: A focus on N estimations. (March 2017) - Aguillaume, L.; Izquieta-Rojano, S.; García-Gómez, H.; Elustondo, D.; Santamaría, J.M.; Alonso, R.; Avila, A.
Abstract: Bulk/wet and throughfall fluxes of major compounds were measured from June 2011 to June 2013 at four Mediterranean holm-oak ( Quercus ilex ) forests in the Iberian Peninsula. Regression analysis between net throughfall fluxes and precipitation indicated that the best defined canopy process was leaching for K + and uptake for NH4 + at all sites. A more variable response between sites was found for Na +, Ca 2+, SO4 2- and Cl −, which suggests that the interplay of dry deposition, leaching and uptake at the canopy was different depending on site climate and air quality characteristics. A canopy budget model (CBM) was used to try to discriminate between the canopy processes and enable to estimate dry deposition and uptake fluxes at three of the sites that complied with the model specifications. To derive N uptake, an efficiency factor of NH4 + vs. NO3 − uptake (xNH4 ) corresponding to moles of NH4 + taken up for each NO3 − mol, has to be determined. Up to now, a value of 6 has been proposed for temperate forests, but we lack information for Mediterranean forests. Experimental determination of N absorption on Quercus ilex seedlings in Spain suggests efficiency factors from 1 to 6. Based on these values, a sensitivity analysis for xNH4 was performed and the NH4 N and NO3 N modeled dry deposition was compared with dry deposition estimated with independent methods (inferential modeling and washing of branches). At two sites in NE Spain under a milder Mediterranean climate, the best match was obtained for xNH4 = 6, corroborating results from European temperate forests. Based on this value, total DIN deposition was 12–13 kg N ha −1 y −1 at these sites. However, for a site in central Spain under drier conditions, variation of the NH4 + efficiency factor had little effect on DD estimates (which ranged from 2 to 2.6 kg N ha −1 y −1 with varying xNH4); when added to wet deposition, this produced a total N deposition in the range 2.6–3.4 kg N ha −1 y −1 . Dry deposition was the predominant pathway for N, accounting for 60–80% of total deposition, while for base cations wet deposition dominated (55–65%). Nitrogen deposition values at the northwestern sites were close to the empirical critical load proposed for evergreen sclerophyllous Mediterranean forests (15–17 kg N ha −1 y −1 ). When organic N deposition at these forests is added (3 kg N ha −1 y −1 ), the total N input to the sites in NE Spain are close to the critical loads for Mediterranean evergreen oak forests. Highlights: A canopy budget model is used to estimate dry deposition and canopy uptake. A sensitivity analysis is carried out to determine NH4 canopy uptake. Dry deposition accounts for 60-80% of total N deposition in 2 oak forests in the NE Iberian Peninsula.